If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(p + -3.5) = 15 Reorder the terms: 2(-3.5 + p) = 15 (-3.5 * 2 + p * 2) = 15 (-7 + 2p) = 15 Solving -7 + 2p = 15 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2p = 15 + 7 Combine like terms: -7 + 7 = 0 0 + 2p = 15 + 7 2p = 15 + 7 Combine like terms: 15 + 7 = 22 2p = 22 Divide each side by '2'. p = 11 Simplifying p = 11
| -2-y=4 | | 2(x-4)+6=22 | | 18(t-3)+3t=7(3t+2)-9 | | -3(m-2)=-5 | | -1(y-20)=2 | | 3(a+b)= | | x+5y=-6 | | m=4m-9 | | -(4y+5)-(-3y-7)=0 | | 15w^3+35w^2+10w=0 | | 49a^2+14a+1=0 | | 5n+17.5-4n=13(n-2)-19.7 | | 67.1=29.7-.2w | | 8x-9-12x=4x-13x-5x | | x=(4480-15y)35 | | 6x+4=10x-8 | | 35x+15y=4480 | | x=-7.5 | | 10x-3-2x=5 | | h^2+18h+81=3 | | -3+4a-7b-7ab= | | -5.2+(-8.3)= | | X^3-2x^2-48x-0=0 | | -.75x-.083333=.666667 | | -.75x-.083=.67 | | -.75x-.25=.67 | | z+35=23 | | -.3+2x=-5.1 | | 3.2=n+3 | | 3(X-4)-2(3X-1)=17 | | -3M^2+48M^2=0 | | 24-x=26 |